.
Ответы
Громова Вероника
10.05.2019 в 03:00

По условию, нам дана функция:  f(x) = (-3 / 5) * x^5 – 2x^4 + (1 / 2) * x^2 + 15.

Будем использовать:

y = f(g(x)), y’ = f’u(u) * g’x(x), где u = g(x).

(x^n)’ = n * x^(n-1).

(c)’ = 0, где c – const.

(√x)’ = (1 / 2) * √x.

(u ± v)’ = u’ ± v’.

(uv)’ = u’v + uv’.

(c * u)’ = с * u’, где с – const.

Таким образом:

f(x)’ = ((-3 / 5) * x^5 – 2x^4 + (1 / 2) * x^2 + 15)’ = ((-3 / 5) * x^5)’ – (2x^4)’ + ((1 / 2) * x^2)’ + 1(5)’ = ((-3 / 5) * 5 * x^4 – 2 * 4 * x^3 + (1 / 2) * 2 * x^1 + 0 = -3x^4 – 12x^3 +x.

Ответ: f(x)’ = -3x^4 – 12x^3 +x.

Заказать реферат
UkrReferat.com. Всі права захищені. 2000-2019